The technical and cost efficiencies of hybrid maize production in western Ethiopia - Alene, D.; Hassan, R.; Demeke, M. (2005)
Conventional farmer efficiency studies have addressed the question of whether possibilities exist for inexpensive gains in production through better use of traditional technology. The question of whether the production potentials of new seed technologies have been fully exploited by poor farmers has rarely been a concern. This paper uses a translog stochastic frontier and inefficiency model to analyze technical efficiency and the factors underlying efficiency differentials among a sample of hybrid maize producers in western Ethiopia. It also uses a dual cost frontier model to compute the cost efficiency of the sample farmers. The results revealed an average technical inefficiency of 25%, showing that farmers actually operate with substantial inefficiency under new technology. This suggests that a considerable maize yield potential remains to be exploited through better use of the technology. An average cost inefficiency of 39% was obtained from the dual model, indicating that farmers could raise the profitability of maize production by 39% by fully adjusting input use. In view of the prevailing high prices of fertilizer against very low price of maize, fertilizer cost inefficiencies among farmers were mainly due to the use of more, rather than less, fertilizer, and this indicates the divergence between economic and biological optimum arising from unfavorable input and output prices facing the farmers. Education, provision of input credit, land tenure, and timely availability of critical inputs are found to be important factors influencing the technical efficiency of maize farmers.